The Interim Trading Skills of Institutional Investors - PUCKETT, ANDY; YAN, XUEMIN (STERLING) (Journal of Finance, 2011)
ABSTRACT Using a large proprietary database of institutional trades, this paper examines the interim (intraquarter) trading skills of institutional investors. We find strong evidence that institutional investors earn significant abnormal returns on their trades within the trading quarter and that interim trading performance is persistent. After transactions costs, our estimates suggest that interim trading skills contribute between 20 and 26 basis points per year to the average fund's abnormal performance. Our findings also indicate that any trading skills documented by previous studies that use quarterly data are biased downwards because of their inability to account for interim trades.